2013
DOI: 10.1021/ct4001119
|View full text |Cite
|
Sign up to set email alerts
|

Fully Integrated Effective Fragment Molecular Orbital Method

Abstract: In this work, the effective fragment potential (EFP) method is fully integrated (FI) into the fragment molecular orbital (FMO) method to produce an effective fragment molecular orbital (EFMO) method that is able to account for all of the fundamental types of both bonded and intermolecular interactions, including many-body effects, in an accurate and efficient manner. The accuracy of the method is tested and compared to both the standard FMO method as well as to fully ab initio methods. It is shown that the FIE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 65 publications
1
63
0
Order By: Relevance
“…Response terms are now included in the FMO gradient for RHF, UHF, MP2, and DFT, and a future promising research direction will be to extend the analytic gradient to other FMO methods, such as multilayer FMO, 47 three-body FMO, 48 FMO with an auxiliary basis set, 49 and the effective fragment molecular orbital method. 50 …”
Section: Discussionmentioning
confidence: 99%
“…Response terms are now included in the FMO gradient for RHF, UHF, MP2, and DFT, and a future promising research direction will be to extend the analytic gradient to other FMO methods, such as multilayer FMO, 47 three-body FMO, 48 FMO with an auxiliary basis set, 49 and the effective fragment molecular orbital method. 50 …”
Section: Discussionmentioning
confidence: 99%
“…61 Issues related to the rigid monomer geometry and its influence on the estimate of T m will be addressed in future studies using the effective fragment molecular orbital (EFMO) method, 62,63 which is based on flexible fragments. It is possible that the EFP method is …”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…For modeling intermolecular interactions, similar strategies based on multipolar expansion have been utilized. [39][40][41] Recently, EFP was combined with fragment molecular orbital (FMO) method 42 giving rise to the EFMO method capable of describing both molecular aggregates and large molecules 43,44 (however, EFMO method has not yet been extended to excited states). Detailed reviews of various flavors of fragment-based methods can be found in Refs.…”
mentioning
confidence: 99%